Investigation of Pore Size Distribution by Mercury Intrusion Porosimetry (MIP) Technique Applied on Different OSB Panels - Ferro, Fabiane Salles; Arroyo, Felipe Nascimento; Castanheira Rodrigues, Edson Fernando; Fraga, Iuri Fazolin; Boff Almeida, Joao Paulo; Ruthes, Heloiza Candeia; Moura Aquino, Vinicius Borges de; Martines Morales, Elen Aparecida [UNESP]; Morato de Moraes, Matheus Henrique; Rocco Lahr, Francisco Antonio; Christoforo, Andre Luis (North Carolina State Univ Dept Wood & Paper Sci, 2021)
Mercury intrusion porosimetry (MIP) is a technique used to characterize the pore size distribution and resin penetration in lignocellulosic materials, such as oriented strand board specimens (OSB), a multilayer panel utilized in structural applications. The method is based on the isostatic injection, under very high pressure, of a non-wetting fluid (mercury) into the porous material to determine parameters such as pore size distribution and percentage of porosity of the specimens. In this study, five different OSB were analyzed; they contained different wood species, resin type, and resin content. The panels manufactured with castor oil polyurethane resin showed porosity values in the range of 54.7 and 27.8%. This was a promising result compared with those obtained for panels made with phenolic resins, which are currently commercialized in Brazil.
Keywords: Mercury porosimetry; Oriented strand board; Castor oil polyurethane resin